Favorable clinical response and drug retention of anti-IL-6 receptor inhibitor in rheumatoid arthritis with high CRP levels: the ANSWER cohort study. (2nd November 2022) - Nakayama, Y; Hashimoto, M; Watanabe, R; Murakami, K; Murata, K; Tanaka, M; Ito, H; Yamamoto, W; Ebina, K; Hata, K; Hiramatsu, Y; Katayama, M; et al.
Abstract : Objective: Currently, biological disease-modifying anti-rheumatic drugs (bDMARDs) with different modes of action [tumour necrosis factor inhibitor (TNFi), interleukin-6 receptor inhibitor (IL-6Ri), or cytotoxic T-lymphocyte antigen 4–immunoglobulin (CTLA4-Ig)] are used in clinical practice to treat rheumatoid arthritis (RA). However, it is unclear which type of bDMARD is the most efficacious for a specific clinical situation. C-reactive protein (CRP) is an acute-phase reactant driven by IL-6 signalling. Here, we aimed to establish whether therapeutic efficacy differs between IL-6Ri and other bDMARDs with alternative modes of action in RA patients according to their CRP level. Method: RA patients treated with bDMARDs were enrolled from an observational multicentre registry in Japan. Patients were classified into three groups according to baseline CRP tertiles. The overall 3 year retention rates of each bDMARD category were assessed. The Clinical Disease Activity Index (CDAI) was also assessed before and 3, 6, and 12 months after bDMARD initiation. Results: A total of 1438 RA patients were included and classified into three groups according to tertiles of baseline CRP levels (CRP 1, 0–0.3; CRP 2, 0.3–1.8; CRP 3, 1.8–18.4 mg/dL). In CRP 3, the overall 3 year drug retention rates were significantly higher for IL-6Ri than for TNFi and CTLA4-Ig (77.5 vs 48.2 vs 67.3, respectively). No significant difference was evident in terms of CDAI 12 months after bDMARD initiation in CRP 1 –CRP 3 . Conclusion: IL-6Ri may be a favourable therapeutic option over TNFi and CTLA4-Ig in RA patients with high CRP levels.